God at war a meditation on religion and warfare - Juergensmeyer, Mark 1940- (Oxford University Press, 2020)
Based on the author's thirty years of fieldwork interviewing activists involved in religious-related terrorist movements around the world, this book explains why desperate social conflict and personal fears lead to extremes of both religion and war, and why invariably God is thought to be engaged in battle. Virtually every religious tradition leaves behind it a bloody trail of stories, legends, and images of war, and most wars call upon the divine for blessings in battle. This book probes the remarkably similar alternative realities that are created in the human imagination by both religious ideas and images of war in response to crises both personal and social
Literaturverzeichnis Seite [97]-101
Keywords: Konfliktforschung; Pazifismus; Kreuzzüge; War; Religious aspects